Task alert through short message service (SMS) case study: Penang Water Authority / Izja Aznie Jelani - Jelani, Izja Aznie (2006)
Task alert through Short Message Service (SMS) was specially designed for Penang Water Authority. Before this there are many pending tasks for the company so that will reduce the employees' performance level. The current process to inform the work order is by sending an email or makes a phone call. The limitations on it such as the employee usually did not open and check the email because of time constraint or the person who responsible is busy and cannot answer the phone calls. This system focuses on alerting the task or work order through SMS. The system also categorizes the employee performance level based on the number of task completed. The user of this system is Penang Water Authority's supervisors, a few numbers of staffs or technicians. This system gives a lot of benefits to the company because the employees will be alerted about the task that they need to do through SMS so it can save time. It is also beneficial to encourage them to increase their productivity. Besides, SMS is available no matter where people are or what they are doing. The flow chart helps to study about the system's activity. Additionally, the context diagram and diagram 0 help the staff to understand the transformation from the traditional types of work order to the electronic work order by alerting them through SMS.